The mill on the Floss - Eliot, George, 1819-1880. (London : Vintage Books, 2010)
Young Maggie Tulliver's loyalty to her beloved older brother, Tom, and to the rest of her family, is tragically tested when she falls in love with the son of her father's bitterest enemy.
Originally published in 1860.
Young Adult
Keywords: Brothers and sisters -- Fiction; Conflict of generations -- Fiction; Vendetta -- Fiction; Water mills -- Fiction; Young women -- Fiction; Conflict of generations -- Fiction; Siblings -- Fiction; Vendetta -- Fiction; Water mills -- Fiction; Young women -- Fiction; England -- Fiction; England -- Fiction